Audit Quality: Does Time Pressure Influence Independence and Audit Procedure Compliance of Auditor? - Firda Ayu Amalia; Sutrisno Sutrisno; Zaki Baridwan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This research was aimed to empirically examine the effect of independence and audit procedure on audit quality with time budget pressure as moderator variable. The population comprised auditors working on Public Accountant Office (KAP) in East Java, while the samples consisted of 45 respondents. This study used a survey technique is by questionnaire as data collection techniques. The PLS was used for data analysis. The result showed that the independence and audit procedure positively affected the audit quality. The variable of time budget pressure as moderator was capable to enfeeble the relation between the independence and audit quality, and also to reinforce the relation between audit procedure and audit quality. The results of this study have provided support for Agency theory. A quality audit can reduce information asymmetry so as to minimize moral hazard actions by management.